A Solution to the Time-Dependent Stress Distribution in Suborbicular Backfilled Stope Interaction with Creeping Rock - Baoxu Yan; Xingping Lai; Hanwen Jia; Erol Yilmaz; Chen Hou (Advances in Civil Engineering)
The creep behavior of deep weak rock masses is important due to an underground opening. Appreciating the nature and source of these deformations requires the knowledge of rock mass and ground support interaction. The theoretical solution of the backfill’s internal stresses needs to consider the time-dependent effect. In the present study, the coupling interaction between the creep behavior of the nearby rock material and the internal stresses in the backfilled stope is considered and the interaction characteristics are given analytically. A solution is then proposed regarding the time-dependent stress distribution in suborbicular backfilled stope interaction with creeping rock. Besides, the correctness of the theoretical solution is verified by numerical simulation, while influential parameters such as stope buried depth, lateral pressure coefficient, horizontal stress ratio, creep time of surrounding rock mass, delay time of the backfill, and Young’s modulus are thoroughly discussed. Research shows that when the stope buried depth becomes large as well as the rheological effect of the nearby rock materials becomes significant, the stress distribution in the backfill material exceeds its self-weight stress and presents significant time-dependent characteristics. The delayed backfilling weakens the backfill’s ground support effect on the nearby rock material. Hence, timely and multipoint simultaneous backfilling is needed for a stope with significant rheological deformation of surrounding rock mass. Lastly, this work will offer useful knowledge while designing the backfill materials for underground mines.